Conversion from Deep Sedation to General Anesthesia in patients undergoing Endoscopic Retrograde Cholangiopancreatography: a series of cases - Costa, Eugênio Araújo; Lima e Souza , Priscila Ferreira de; Poma , Mara Aparecida Maricato; Fernandes, Cláudia Regina; Carneiro , Fred Olavo Aragão Andrade; Nobre e Souza , Miguel Ângelo (Brazilian Journal of Case Reports, 2021)
Not applicable.